Perinatal Care of Childhood Sexual Abuse Survivors: Scoping Review. Issue 3 (May 2022) - Head, Morgan L.; Heck, Jennifer L.
Abstract: Background: An estimated one in nine women seeking perinatal care is a survivor of childhood sexual abuse (CSA), yet CSA may be unknown to nurses and other health care providers. Childhood sexual abuse can have adverse physical and psychological effects for survivors, and the intimacy of perinatal care can trigger distress like intrusive thoughts. Purpose: To explore available literature about CSA survivors and perinatal care. Specific aims were to 1) identify nursing actions that ease undesirable feelings during perinatal care for CSA survivors and 2) identify gaps in the literature on perinatal care for CSA survivors. Study Design and Methods: Following the PRISMA-ScR Checklist, MEDLINE and CINAHL databases were searched using: "Child Abuse, Sexual, " "Perinatal Care, " and "Parturition." Initial yield was 109 records. Results: Applying inclusion and exclusion criteria produced 14 full-text articles. Findings suggest that obtaining consent, promoting safety, trust, and control, fostering a healthy nurse–patient relationship, and inquiring about abuse may improve how CSA survivors experience perinatal care. Gaps in literature include nursing assessments for history of CSA with nonverbal cues. Clinical Implications: For all patients, nurses should foster security and trust. It is critical that CSA survivors be in control of their care. Procedures should be thoroughly explained, and most importantly, consent should be obtained prior to every physical touch. Nurses must ask about history of CSA because it is part of patient-centered care, which is central to nursing. Abstract : Survivors of childhood sexual abuse need sensitive nursing care during labor and birth. Procedures and exams may be triggering of the abuse. Consent to touch is critical. In this scoping review of perinatal care of childhood survivors of sexual abuse, voices of women are highlighted and their suggestions for how to improve care during the childbirth process are identified. Experiences of survivors of childhood sexual abuse when receiving maternity care need more research to promote safe and effective perinatal nursing care for this vulnerable population.